Promotion paths for regional public brand development of agri-products in urban areas: resource and institutional perspectives - Xu, Pu; Huang, Jie; Liu, Min; Li, Yufeng (Frontiers in Sustainable Food Systems, 2024)
This study aimed to find the determinants of regional public brand development of agri-products in urban areas and to explore the specific enhancement paths for the regional public brand development of agri-products. The regional public brand of agri-products in Shanghai was selected as the research object. The study utilized stratified and random sampling techniques to collect data from 320 questionnaires of agricultural business entities in Shanghai. Then a covariance-based structural equation model with institutional factors as mediating variables was constructed. Furthermore, the study empirically analyzed the mechanism of the role of resource endowment on regional public brand development of agri-products. The study showed that the main factors affecting regional public brand development of agri-products are market maintenance, public marketing, industrial resources, and regional resources, in order of importance. Regional and industrial resources positively affected agricultural regional public brand development through the masking effect of public marketing and the partially mediating role of market maintenance. Among them, market maintenance reversed the significant negative impact of regional resources on the regional public brand development of agri-products. The findings of the study contribute to enriching the existing theoretical literature on regional public branding of agri-products, and provide practical implications for the government to help formulate and improve regional brand development policies in urban areas.